PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR TBK PERIODE 2018-2022 (Studi Kasus Perusahaan Manufaktur Sub Sektor Logam dan Sejenisnya yang terdaftar di Bursa Efek Indonesia) - An’nisa Hanan Santoso, Vivi; Syakhrial (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Current Ratio, Debt to Equity Ratio, and Return On Equity on the share price of manufacturing companies in the metal sub-sector and others registered on the Indonesia Stock Exchange for the period 2018 to 2022. Methodology used is multiple regression with panel data from companies that fulfill the specified criteria. The results show partial, Current Ratio obtained a t-statistic of 5,954470 > 2,06866 and prob. of 0.000 <0.05 and Debt to Equity Ratio obtained a t-statistic of 2,799004 > 2,06866 and prob. of 0.0108 < 0.05, meaning that Current Ratio and Debt to Equity Ratio show a significant effect on share prices, while Return On Equity obtained a t-statistic of 0,687779 < 2,06866 and prob. of 0.4991 > 0.05, meaning it has no effect on share prices. Simultaneously, Current Ratio, Debt to Equity Ratio, and Return On Equity significantly affect the share price. Based on the coefficient of determination test results, R square value of 0,631057or 63,1057% and adjusted R-squared value of 0,578351 or 57,8351%. So it can be concluded that the independent variables consisting of Current Ratio (X1), Debt to Equity Ratio (X2), and Return On Equity (X3) are able to explain the dependent variable, the share price by 57,8351%, while the remaining 42,1649% (100 - adjust R squared value) is explained by other variables that are not included in this research model.